2011
DOI: 10.1111/j.1574-6968.2011.02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Model of the molecular basis for hydroxylamine oxidation and nitrous oxide production in methanotrophic bacteria

Abstract: Many methane-oxidizing bacteria (MOB) have been shown to aerobically oxidize ammonia and hydroxylamine (NH(2)OH) to produce nitrite and nitrous oxide (N(2)O). Genome sequences of alphaproteobacterial, gammaproteobacterial, and verrucomicrobial methanotrophs revealed the presence of haoAB, cytL, cytS, nirS or nirK, and norCB genes that may be responsible for N(2)O production, and additional haoAB genes were sequenced from two strains of Methylomicrobium album. The haoAB genes of M. album ATCC 33003 were inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 29 publications
4
79
0
Order By: Relevance
“…Many of these organisms harbor at least one HAO-like protein that has an elusive role. It was suggested that these HAO-like proteins could either oxidize hydroxylamine to nitrite or NO or alternatively reduce nitrite to NO (61,62). Despite substantial sequence divergence, HAO-like proteins from methane oxidizers have two prominent features in common with kustc1061 and its homologs in anammox bacteria: they do contain the tyrosine involved in the covalent binding of the catalytic heme that favors oxidative reactions and lack the tyrosine present in NeHAO (Tyr 358 ; supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these organisms harbor at least one HAO-like protein that has an elusive role. It was suggested that these HAO-like proteins could either oxidize hydroxylamine to nitrite or NO or alternatively reduce nitrite to NO (61,62). Despite substantial sequence divergence, HAO-like proteins from methane oxidizers have two prominent features in common with kustc1061 and its homologs in anammox bacteria: they do contain the tyrosine involved in the covalent binding of the catalytic heme that favors oxidative reactions and lack the tyrosine present in NeHAO (Tyr 358 ; supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genes for nitrite reduction (nirS) and nitric oxide reduction (norB) were predicted. A gene encoding cytochrome P460 was predicted, indicating a potential for hydroxylamine detoxification (4,6).…”
mentioning
confidence: 99%
“…A gene homologous to hydroxylamine oxidoreductase (hao), possibly handling hydroxylamine toxicity arising from oxidation of ammonia by pMMO, is present (2).…”
mentioning
confidence: 99%